Food-Based Dietary Guidelines – development of a conceptual framework for future Food-Based Dietary Guidelines in Europe: report of a Federation of European Nutrition Societies Task-Force Workshop in Copenhagen, 12–13 March 2018. Issue 12 (28th December 2020) - Tetens, Inge; Birt, Christopher A.; Brink, Elizabeth; Bodenbach, Stephanie; Bugel, Susanne; De Henauw, Stefaan; Grønlund, Trine; Julia, Chantel; Konde, Åse Bonde; Kromhout, Daane; Lehmann, Undine; dos Santos, Quenia; et al.
Abstract: Identifying a need for developing a conceptual framework for the future development of Food-Based Dietary Guidelines (FBDG) in Europe, The Federation of European Nutrition Sciences established a Task Force for this purpose. A workshop was held with the specific objective to discuss the various dimensions considered as particularly relevant. Existing frameworks for FBDG were discussed, and presentations from various countries illustrated not only several commonalities but also a high degree of heterogeneity in the guidelines from different countries. Environmental aspects were considered in several countries, and dimensions like food safety, dietary habits and preparation were included in others. The workshop provided an overview of the use of FBDG – both in developing front-of-pack nutrition labels and for reformulation and innovation. The European FBDG dimensions were described with examples from the close connection between FBDG and European Union (EU) policies and activities and from the compilation of a database of national FBDG. Also, the challenges with communication of FBDG were discussed. Considering the current scientific basis and the experiences from several countries, the Task Force discussed the various dimensions of developing FBDG and concluded that environmental aspects should be included in the future conceptual framework for FBDG. A change in terminology to sustainable FDBG (SFBDG) could reflect this. The Task Force concluded that further work needs to be done exploring current practice, existing methodologies and the future prospects for incorporating other relevant dimensions into a future Federation of European Nutrition Societies conceptual framework for SFBDG in Europe and working groups were formed to address that.